2020
DOI: 10.3892/ol.2020.11761
|View full text |Cite
|
Sign up to set email alerts
|

Structure identification, antitumor activity and mechanisms of a novel polysaccharide from Ramaria flaccida (Fr.) Quél

Abstract: It is an important aspect of current cancer research to search for effective and low-toxicity anticancer drugs and adjuvants. Polysaccharides, as immunomodulators, can improve the immune function of the body, kill tumor cells directly and prevent tumor development by increasing the resistance of the body to carcinogenic factors. The aim of the present study was to identify natural polysaccharide compounds with novel structure and antitumor activity via the separation and analysis of polysaccharide components f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…The relative molar percent were 40.61%, 26.97%, 17.72%, 7.78%, 6.31%, 0.11%, 0.06% and 0.44% (Table 1). This was consistent with previous literature which suggested that Ramaria polysaccharides mainly consist of glucose, galactose, and mannose (Bhanja et al, 2013; Dong et al, 2020; Li, 2017). Beyond that, proteins and sulfates separately took up 8.18% and 4.12% of DRFP mass.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The relative molar percent were 40.61%, 26.97%, 17.72%, 7.78%, 6.31%, 0.11%, 0.06% and 0.44% (Table 1). This was consistent with previous literature which suggested that Ramaria polysaccharides mainly consist of glucose, galactose, and mannose (Bhanja et al, 2013; Dong et al, 2020; Li, 2017). Beyond that, proteins and sulfates separately took up 8.18% and 4.12% of DRFP mass.…”
Section: Resultssupporting
confidence: 93%
“…According to the calibration curve connecting the Mw and elution volume of Dextran T‐series, the Mw of DRFP was calculated to be 101.68 kDa. The Mw was lower than immunoenhancing glucan from R. botrytis (Bhanja et al, 2013), and much higher than the antitumor polysaccharide from R. flaccida and antioxidant polysaccharides from R. botrytis (Dong et al, 2020; Li, 2017). This difference might be explained by differences in the strains or growth conditions.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Some Ramaria fruiting bodies are considered to be poisonous, including Ramaria flavo-brunnescens and Ramaria rufescens (Huang et al 2009 ; Perez-Moreno and Ferrera-Cerrato 1995 ; Scheid et al 2022 ), while other Ramaria species are edible, such as Ramaria botrytis , Ramaria madagascariensis , Ramaria largentii , Ramaria flava , and Ramaria formosa (Aprotosoaie et al 2017 ; Khaund and Joshi 2014 ; Liu et al 2014 , 2015 ). Polysaccharide, sesquiterpenes, and glucan extracted from the basidiocarps of Ramaria exhibited antioxidant, antigenotoxic, antitumor, antimicrobial, and immunoenhancing activities (Barros et al 2008 ; Bhanja et al 2013 ; Centko et al 2012 ; Dong et al 2020 ; Fu et al 2022 ; Li 2017 ; Liu et al 2013 ; Zou et al 2021 ). All in all, the accurate identification and classification of Ramaria species is very important for the development and utilization of Ramaria species.…”
Section: Introductionmentioning
confidence: 99%